Impacts of Domestic Joint Ventures on Industrial Rates of Return: A Pooled Cross-Section Analysis, 1964-1975 - Berg, Sanford V.; Friedman, Philip (The Review of Economics and Statistics, 1981)
Sanford V. Berg, Philip Friedman, Impacts of Domestic Joint Ventures on Industrial Rates of Return: A Pooled Cross-Section Analysis, 1964-1975, The Review of Economics and Statistics, Vol. 63, No. 2 (May, 1981), pp. 293-298